PERDEBATAN HAK CIPTA ATAS KARYA KECERDASAN BUATAN (AI): MENUJU KERANGKA HUKUM ADAPTIF YANG MENDUKUNG INOVASI TEKNOLOGI - Maxmiliano, Petrus; Hartanto, Michael Phrigyan; Mahendrasusila, Fernandi; Oentoro, Benaya Azareel (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
In the digital era, artificial intelligence (AI) has become a pivotal tool in generating creative works. However, the debate over copyright for AI-generated works has emerged as a critical issue requiring attention. This article explores the challenges of originality and ownership in AI-generated works and the legal approaches applicable. By adopting a literature analysis method from national and international journals, this study finds that current copyright frameworks inadequately address AI-created works. Proposed solutions include the development of specific laws and ethical frameworks to ensure copyright protection without stifling technological innovation. The study highlights that while AI-generated works hold significant potential, effective copyright protection necessitates an adaptive legal approach. This research concludes that updating copyright regulations is essential to align with advancements in AI technology.